PROBLEMA PERNIKAHAN USIA DINI (Suatu Tinjauan Multi Dimensi) - Muh. Haras Rasyid (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
Early marriage is the marriage of a man or a woman who has not reached age according to the civil laws and regulations in Indonesia. Early marriage is one of the problems at marriage it self, because on the one hand as citizens it is a require to obey the laws and regulations that limit the minimum age at 19 years old for men and 16 years old for women. And the other hand, in the teachings of Islam marriage is legitimate if both are already baligh Even though they has not reached 19 and 16 years yet. This paper provides several reviews specifically as review of Islamic law, social review and economic review. With these reviews, besides to providing an understanding of the importance from marriage also gives the knowledge about maslahat and mudharat that occur in early marriage, on aspect of legislation, religion, economics and social.